The activation of antiviral RNA interference not only exists in neural progenitor cells but also in somatic cells in mammals - Yuqiang Zhang; Zhe Li; Zhi Ye; Yan Xu; Binbin Wang; Congcong Wang; Yunpeng Dai; Jinfeng Lu; Boxun Lu; Wanju Zhang; Yang Li (Taylor & Francis, 2020)
The RNA interference (RNAi) pathway directs an important antiviral immunity mechanism in plants and invertebrates. Recently, we and others have demonstrated that the antiviral RNAi response is also conserved in mammals, at least to five distinct RNA viruses, including Zika virus (ZIKV). ZIKV may preferentially infect neuronal progenitor cells (NPCs) in the developing foetal brain. Ex vivo ZIKV infection induces RNAi-mediated antiviral response in human NPCs, but not in the more differentiated NPCs or somatic cells. However, litter is known about the in vivo property or function of the virus-derived small-interfering RNAs (vsiRNAs) targeting ZIKV. Here we report a surprising observation: different from ex vivo observations, viral small RNAs (vsRNAs) targeting ZIKV were produced in vivo upon infection in both central neuron system (CNS) and muscle tissues. In addition, our findings demonstrate the production of canonical vsiRNAs in murine CNS upon antiviral RNAi activation by Sindbis virus (SINV), suggesting the possibility of antiviral immune strategy applied by mammals in the CNS.
Keywords: Space Science; Medicine; Cell Biology; Genetics; Molecular Biology; Neuroscience; Immunology; Developmental Biology; Cancer; Mental Health; Infectious Diseases; Virology; Computational Biology